2018
DOI: 10.1038/s41598-018-23034-w
|View full text |Cite
|
Sign up to set email alerts
|

ILF2 and ILF3 are autoantigens in canine systemic autoimmune disease

Abstract: Dogs can spontaneously develop complex systemic autoimmune disorders, with similarities to human autoimmune disease. Autoantibodies directed at self-antigens are a key feature of these autoimmune diseases. Here we report the identification of interleukin enhancer-binding factors 2 and 3 (ILF2 and ILF3) as autoantigens in canine immune-mediated rheumatic disease. The ILF2 autoantibodies were discovered in a small, selected canine cohort through the use of human protein arrays; a method not previously described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Most biomarker studies analyzed small case cohorts (24/49), 65 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 18 studies were midsized, 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 and 7 were large. 66 , 108 , 109 , 110 , 111 , 112 , 113 We observed a variety of approaches for phenotyping and classifi...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most biomarker studies analyzed small case cohorts (24/49), 65 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 18 studies were midsized, 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 and 7 were large. 66 , 108 , 109 , 110 , 111 , 112 , 113 We observed a variety of approaches for phenotyping and classifi...…”
Section: Resultsmentioning
confidence: 99%
“… 79 , 86 A few studies cited data from smaller nested pilot studies in addition to reporting the findings of their larger study. 108 , 113 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ILF3 interacts with Nanog homeobox mRNA to regulate pluripotency in embryonic stem cells and has potential roles in sustaining embryonic stem cell self-renewal and cell fate determination (28). While a previous study indicated that ILF3 expression may be a novel risk factor for venous thromboembolism, stroke and coronary artery disease (29), ILF3 autoantibodies have been identified as potential diagnostic biomarkers for human autoimmune disease (30). Furthermore, ILF3 interacts with interleukin-2 in T cells to upregulate synoviolin in rheumatoid synovial cells and is therefore a potential therapeutic target for rheumatoid arthritis (31).…”
Section: Discussionmentioning
confidence: 99%
“…They are more common in pure breeds than mixed breeds and in female dogs than male dogs (Gorman & Werner, 1986 ; Pedersen, 1999 ). In veterinary medicine, genetic factors are implicated in the development of MAS, and several studies have been conducted in certain breeds (Bremer et al., 2018 ; Day & Penhale, 1992 ; Pedersen et al., 2012 ). However, our understanding about MAS in dogs is still inadequate.…”
Section: Introductionmentioning
confidence: 99%